Establishment, spread, and impact of Teretriosoma nigrescens (Coleoptera: Histeridae), an exotic predator of the larger grain borer (Coleoptera: Bostrichidae) in southwestern Benin - Borgemeister, C.; Djossou, F.; Adda, C.; Schneider, H.; Djomamou, B.; Degbey, P.; Azoma, B.; Markham, R.H. (Oxford University Press, 1997)
Studies were carried out between 1992 and 1997 in southwestern Benin to investigate the establishment, spread, and impact of Teretriosoma nigrescens Lewis, a natural enemy of the larger grain borer, Prostephanus truncatus (Horn). Trap data, using the 2-component synthetic aggregation pheromone of P. truncatus , from 5 different surveys, carried out twice yearly over a 3-yr period, showed a rapid establishment and spread of the predator throughout the region. Increasing numbers of T. nigrescens in the pheromone traps were associated with decreasing numbers of P. truncatus . Pheromone trap data, collected weekly at a small number of sites over the entire study period, revealed a yearly bimodal peak in flight activity of P. truncatus in 1992, 1993, and 1994. The 1st peak in flight activity of P. truncatus was sharply reduced in 1995, 1996, and 1997, accompanied by increasing numbers of T. nigrescens in the pheromone traps. Data from on-farm storage experiments and from surveys in farm-stored maize, Zea mays L., showed a considerable reduction of P. truncatus infestation, and decreasing losses of maize, coinciding with the increasing presence of T. nigrescens.